2018
DOI: 10.4155/fsoa-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterization of Stem Cell and Differentiation Markers of the Dental Pulp of Human Natal Teeth

Abstract: Aim:Dental pulp stem cells, which are primarily derived from the pulp tissues of human teeth, have rarely been obtained from natal teeth. This study investigated the stem cell and differentiation markers of the dental pulp of natal teeth using immunohistochemistry.Materials & Methods:The pulp tissue from extracted natal teeth (n = 2) of a 20-day-old healthy male was examined for immunohistochemical expression of stem cell (Oct-4 and SOX 2) and differentiation markers (Nestin, CD 44, desmin, osteopontin and Ki-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A previous study reported that in dental papilla cells, SOX2 was absent during the bud stage, but became evident, following the formation of enamel and dentin [ 15 ]. In human natal teeth, the strong expression of SOX2 is detected in the pulp tissue [ 36 ]. Notably, a recent study reported that overexpressing SOX2 in dental pulp stem cells (DPSCs) help promote odontoblastic differentiation and enhance the production of dentin sialoprotein (DSPP) and dentin matrix protein-1 (DMP) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that in dental papilla cells, SOX2 was absent during the bud stage, but became evident, following the formation of enamel and dentin [ 15 ]. In human natal teeth, the strong expression of SOX2 is detected in the pulp tissue [ 36 ]. Notably, a recent study reported that overexpressing SOX2 in dental pulp stem cells (DPSCs) help promote odontoblastic differentiation and enhance the production of dentin sialoprotein (DSPP) and dentin matrix protein-1 (DMP) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuating expression of Nanog in adult and primary teeth dental pulp cells has been previously reported to reflect the differentiation status of the cells. 50 Sox2 is a marker of uncommitted neuroepithelium and has previously been found in association with dental pulp in vivo 51 and DPSCs in vitro. 42 with DPSCs after global ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…We tested multiple stem cell markers such as OCT3/4, PAX7, SOX2, CD34 and aSMA finding the same de-differentiation markers in both pulp and PDL and these markers increased after giving the drug. These markers could be due to the dedifferentiation of mature cells (1)(2)(3)21,24) or could be markers of stem cell populations in the pulp and PDL as discussed above (72). Cross talk between the pulp and the periodontal ligament should not be ruled out since the pulp and PDL are anatomically connected via the apical root vasculature.…”
Section: Induction Of Stem Cell Markersmentioning
confidence: 99%